Effect of hybrid reinforcement on the performance of filament wound hollow shaft. (15th January 2018) - Tariq, Mateen; Nisar, Salman; Shah, Aqueel; Akbar, Sohaib; Khan, Muhammad Ali; Khan, Sohaib Zia
Abstract: Previous studies have shown that composite materials can replace metals as the material of construction in shafts. Composite material shafts are normally made up of polymer matrix composites as they are easy to design and economical to manufacture. This paper investigates the effect of hybrid reinforcement on the performance of filament wound hollow shaft. The hybrid shafts are composed of hybrid filaments including a combination of carbon, glass and aramid fibers. The initial stage involved development and verification of FEA model in order to establish grounds for further experimentation. Afterwards, a design of experiments model was established and experiments were performed using FEA. After the design phase, the shafts were manufactured using filament winding processing technique employing suitable matrix and reinforcement systems. Lastly, the shafts were tested for torsional characteristics, hardness, density and chemical reactivity. The results showed that carbon fiber reinforcement shows best results in terms of torsional characteristics. In terms of chemical reactivity, carbon-glass hybrid reinforcement exhibited minimum degradation. Furthermore, it was also found that hybrid reinforcements containing carbon-aramid fibers showed better results in terms of density and surface hardness.